KARAKTERISTIK BIOLOGI DAN KIMIA TANAH SAWAH AKIBAT PEMBAKARAN JERAMI - Annisa Tommy; Mukhlis Mukhlis; Benny Hidayat (Jurnal Agroekoteknologi, 2014)
The aim of this research was to study the biological and chemical characteristics of paddy soilcaused of burning rice straw. This research was conducted in Subdistrict Tanjung Morawa, DistrictDeli Serdang, North Sumatera Province. Sampling was done at the public rice field with strawburning over it and Balai Benih Sari Murni which never burning straw. Soil samples were takenunder the heap of burnt straw in three times, i.e after burning soon (0 week after harvesting), 1 and2 week after harvesting to analyze the number of arthropod an microorganisms, soil colour, texture,pH, C-organic, N-total, P-available, and K-exchangable in The Soil Biology, Soil Chemical andFertility, and Research and Technology Laboratory, Agricultural Faculty of North SumateraUniversity, Medan. The results showed that the soil with straw burning over it has the number ofarthropod and microorganism, C-organic, N-total, and P-available is lower than the unburnt soil. pHand K-exchangeable of the burnt soil is higher than the unburnt soil. In 2 weeks afterburning, the number of arthropod and microorganism, C-organic, and P-available gets recoveryfrom before.